A study of the thermodynamics and mechanisms of the atmospherically relevant reaction dimethyl sulphide (DMS) with atomic chlorine (Cl) in the absence and presence of water, using electronic structure methods. Issue 6 (24th January 2023) - Rhyman, Lydia; Lee, Edmond P. F.; Ramasami, Ponnadurai; Dyke, John M.
Abstract : The figure shows the TS, formed from DMS·H2 O + Cl, that corresponds to the pathway with the largest rate coefficient in the presence of water. Abstract : The thermodynamics and mechanisms of the atmospherically relevant reaction dimethyl sulphide (DMS) + atomic chlorine (Cl) were investigated in the absence and presence of a single water molecule, using electronic structure methods. Stationary points on each reaction surface were located using density functional theory (DFT) with the M06-2X functional with aug-cc-pVDZ (aVDZ) and aug-cc-pVTZ (aVTZ) basis sets. Then fixed point calculations were carried out using the UM06-2X/aVTZ optimised stationary point geometries, with aug-cc-pVnZ basis sets (n = T and Q), using the coupled cluster method [CCSD(T)], as well as the domain-based local pair natural orbitals coupled cluster [DLPNO-UCCSD(T)] approach. Four reaction channels are possible, formation of (A) CH3 SCH2 + HCl, (B) CH3 S + CH3 Cl, (C) CH3 SCl + CH3, and (C′) CH3 S(Cl)CH3 . The results show that, in the absence of water, channels A and C′ are the dominant channels. In the presence of water, the calculations show that the reaction mechanisms for A and C formation change significantly. Channel A occurs via submerged TSs and is expected to be rapid. Channel B occurs via TSs which present significant energy barriers indicating that this channel is not significant in the presence of water relative to CH3 SCH2 + HCl and DMS·Cl adduct formation, as is the case in the absence of water. Channel C was not considered as it is endothermic in the absence of water. In the presence of water, pathways which proceed via (a) DMS·H2 O + Cl, (b) Cl·H2 O + DMS and (c) DMS·Cl + H2 O were considered. It was found that under tropospheric conditions, reactions via pathway (b) are of minor importance relative to those that proceed via pathways (a) and (c). This study has shown that water changes the mechanisms of the DMS + Cl reactions significantly but the presence of water is not expected to affect the overall reaction rate coefficient under atmospheric conditions as the DMS + Cl reaction has a rate coefficient at room temperature close to the collisional limit.